Geochemistry, grain size and radiocarbon ages of MIS 3 sediment record from Nesseltalgraben, Germany - Christoph Mayr; Philipp Stojakowits; Bernhard Lempe; Maarten Blaauw; Volker Diersche; Madleen Grohganz; Matthias López Correa; Christian Ohlendorf; Paula J Reimer; Bernd Zolitschka (PANGAEA, 2020)
Continuous sediment profiles were taken from ravine slopes at the Nesseltalgraben site in the Northern Calcareous Alps (SE Germany, 47.6567°N 13.0467°E, 560-582 m a.s.l.) in October 2016. The profile consists of fine-grained lacustrine-palustrine sediments overlain by several metres of glacifluvial gravels and lodgement tills of the Last Glacial Maximum and underlain by a diamicton. High-resolution (2 mm steps) element counts (Ca, S, Si, K, Ti, Mn, Fe, Zn, Rb, Sr, Zr) were obtained with an XRF core scanner (Itrax, Cox Analytical Systems, Sweden). Organic geochemistry (total organic and inorganic carbon, total nitrogen, total sulphur) was analysed with an elemental analyser (Euro EA, Eurovector, Germany), grain size with a laser diffractometer (Beckman-Coulter LS 200). The sediment profiles were compiled to a composite record of 21?m length. The age model bases on 29 radiocarbon analyses of macroscopic terrestrial plant remains (byrophytes, plant debris, monocots, wood, and twigs) and a previously discovered paleomagnetic anomaly assigned to the Laschamp event. The age model covers the period 59 to 29.6 ka cal BP and assigns the record to Marine Isotope Stage (MIS) 3. The sediment record shows rapid changes in lithology, sedimentology, and geochemistry related to Dansgaard-Oeschger climatic events.